2020
DOI: 10.1038/s41598-020-63836-5
|View full text |Cite
|
Sign up to set email alerts
|

Tempo-spatial variations of the Ryukyu Current southeast of Miyakojima Island determined from mooring observations

Abstract: The origin, structure, and variability of the Ryukyu Current (RC) have long been debated, mostly due to limited observations. A mooring array, deployed for two years southeast of Miyakojima in the southern portion of the Ryukyu Island chain, has provided, for the first time, data confirming the existence and revealing the characteristics of the RC in that upstream region, including its velocity structure and variability. The observations show a shoreward-intensified current flowing northeastward, with a subsur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…To further evaluate the capability of the HYCOM reanalysis in the upstream Ryukyu Current, we used two sets of current‐measuring mooring systems belonging to an international cooperative research project “Joint Kuroshio and Ryukyu Current System Study” (JKRYCSS, Zhao et al., 2020). These two stations, RCM2 and RCM3, were positioned on the Ryukyu Current path southeast of Miyakojima from June 2015 to June 2017 (Figure 1b), with RCM2 near the Ryukyu Current core and RCM3 near the edge (Figure 2b).…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…To further evaluate the capability of the HYCOM reanalysis in the upstream Ryukyu Current, we used two sets of current‐measuring mooring systems belonging to an international cooperative research project “Joint Kuroshio and Ryukyu Current System Study” (JKRYCSS, Zhao et al., 2020). These two stations, RCM2 and RCM3, were positioned on the Ryukyu Current path southeast of Miyakojima from June 2015 to June 2017 (Figure 1b), with RCM2 near the Ryukyu Current core and RCM3 near the edge (Figure 2b).…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…Kikai Island is located along the path of the Kuroshio and Ryukyu currents, where mesoscale eddies propagating from the Pacific cause complex current variability (Nagano et al, 2007;Zhao et al, 2020). In addition, due to the existence of seamounts and small islands in the Tokara Strait near Kikai Island, turbulent mixing induced by these abrupt topographical features may influence Kikai ocean currents (Chang et al, 2016;Hasegawa et al, 2021;Ichikawa, 2001;Kobari et al, 2020;Nagai et al, 2019Nagai et al, , 2021Tanaka et al, 2021;Tsutsumi et al, 2017).…”
Section: Coral Sampling Locationmentioning
confidence: 99%
“…Recently, the high‐resolution systematic oceanic investigation for the KC by Argo profiling floats, covering the last 20 years. The observation and research of the RC started even later, and observational data were obtained only after the 1990s (Andres et al., 2008; Ichikawa et al., 2004; Jin et al., 2010; Liu et al., 2022; Nagano et al., 2007; Thoppil et al., 2016; Zhao et al., 2020; Zhu et al., 2006). These data cannot provide oceanic information regarding climate changes such as El Niño‐Southern Oscillation (ENSO) and Pacific Decadal Oscillation (PDO) and hence other proxies are necessary to reconstruct long‐term variation of the Kuroshio and Ryukyu currents.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigation shows that the HR models largely reproduces the observed KRS characteristics, including the ECS‐Kuroshio with transport of 25 Sv across PN section and the 12 Sv Ryukyu Current with core locating at 500 m across RN section (Figures 2a and 2c), consisting well with observations and reanalysis data (Table S2 in Supporting Information ). In addition to PN and RN, two additional sections, PCM1 and RCM1, are also involved to describe the upstream KRS (Johns et al., 2001; Zhao et al., 2020; location of the sections are shown in Figure 1a). It is found that the ECS‐Kuroshio exhibits a 21 Sv transport across PCM1 section and the Ryukyu Current displays a 6 Sv transport across RCM1 section, both are consistent with observation/reanalysis values.…”
Section: Enhanced Ecs‐kuroshio and Disappearing Ryukyu Current Under ...mentioning
confidence: 99%